Progressive language impairment without dementia: a case with isolated category specific semantic defect. Issue 9 (September 1988) - Basso, A; Capitani, E; Laiacona, M
Abstract : A patient is described with a 5 year progressive defect of naming and auditory verbal comprehension, the pathological nature of which was presumably degenerative. The auditory comprehension defect unevenly affected different semantic categories, and was particularly severe for the names of animals, fruits and vegetables. The patients showed loss of the verbal knowledge of the physical attributes of the concepts corresponding to the words he was unable to understand, and sparing of the verbal knowledge of the functional attributes. His performance was defective also on the colour-figure and sound-picture matching test.